GENRE KNOWLEDGE AND WRITING DEVELOPMENT OF GRADUATE STUDENTS MAJORING IN SOFT AND HARD SCIENCES IN COMPOSING RESEARCH ARTICLE INTRODUCTIONS - Dian Setiawati, - (2023)
Abstract Studies on genre knowledge have been done extensively ranging from the conceptualization of genre knowledge, the effects of genre knowledge in a writing class, and prior genre knowledge and writing strategies. However, only a few focus on the relation between genre knowledge and writing development. On the other hand, many studies have explored the rhetorical move analysis of research article introductions written by authors across disciplines. Nevertheless, little is known about the relation between genre knowledge and the writing development of students across disciplines in writing research article introductions. Thus, this study aims to analyze and compare genre knowledge and writing development of Indonesian graduate students from soft and hard sciences in composing their research article introductions. A total of 12 research article introductions written in English by four graduate students of a public university in West Java were purposively selected as the corpus of this qualitative study. Swales' (2004) revised Creating a Research Space (CARS) framework was used to analyze the research article introductions, while Tardy's (2009) Genre Knowledge was used to formulate in dept interview questions. The findings revealed that Indonesian graduate students majoring in soft and hard sciences shared similarities and differences in organizing their research article introductions. Furthermore, Indonesian graduate students' genre knowledge was manifested in their actual writing. Students' genre knowledge was also associated with their writing development. Additionally, some other related issues contributed in influencing students' writing development. Pedagogical implications and recommendations for further studies are also discussed. Keywords: Genre knowledge, writing development, research article introduction, move analysis, soft and hard sciences